K file : The conspiracy of silence A Brave book of Kashmir - Assad, Bashir (New Delhi Vitasta Publishing, 2019)
The conflict in Jammu and Kashmir is one of the biggest internal security challenges for the Indian state. 2001 saw over 4, 500 terror-related deaths in the state.This figure has steadily declined in the last 18 years, making the world wrongly believe this reduction in violence is a sign that Kashmir is moving towards conflict resolution., bashir assad argues, there is never going to be a resolution of conflict in Kashmir and return to peace unless all stakeholders --- The Kashmiris themselves, the Indian state and the political parties in Kashmir get together and negotiate peace with the militants.The ideology of holy jihad and the aspiration for the kingdom of God has now coopted women and teenagers as their strongest campaigner in Kashmir, turning paradise into hell. The change from a political problem to a religious matter needs to be understood and strategically challenged, the activist-journalist says in his brave book, K file-the conspiracy of silence.
Keywords: Kashmir-Politics and government; Kashmir Militancy; Kashmir-Peace and violence